Sex, Culture, and the Biology of Rape: Toward Explanation and Prevention - Jones, Owen D. (1999)
For all that has been written about rape, its multiple causes remain insufficiently understood for law to deter it effectively. This follows, in part, from inadequately interdisciplinary study of rape causation. This Article argues that integrating life science and social science perspectives on sexual aggression can improve law's model of rape behavior, and further our efforts to reduce its incidence. The Article first explains biobehavioral theories of sexual aggression, and offers a guide to common but avoidable errors in assessing them. It then compares a number of those theories' predictions with existing data and demonstrates how knowledge of the effects of evolutionary processes on human behavioral predispositions may help us better understand - without justifying or excusing - psychological mechanisms that contribute to patterns of rape. Because increased knowledge of causal influences may afford law increased effectiveness in deterring rape, the author then explores ways in which bio-behavioral theories could affect analysis of several current legal issues, from the debate over chemical castration to the meaning of motive in rape-relevant legislation